{Central causes of menstrual disturbances: Delving into deep neurosurgical waters: A report of 3 cases} - Aliakiozoglou, I.; Charalambides, C.; Papaioannou, G.; Michala, L. (Journal of Reproductive Medicine, 2017)
© Journal of Reproductive Medicine®, Inc. BACKGROUND: Menstrual disorders are common in adolescence and are usually caused by an immature hypothalamic-pituitary-ovarian axis. Occasionally, suppressed gonadotropins or a raised prolactin may raise suspicion for a central organic cause of amenorrhea. CASE: We present the cases of 3 adolescents with menstrual irregularities or amenorrhea who were found to have hypothalamic gliomas (2 cases) and a craniopharyngioma (1 case). An MRI of the brain revealed the diagnosis in all 3 cases. CONCLUSION: Although rare, brain disease should be included in the differential diagnosis of menstrual irregularities, particularly in cases of central delayed puberty, moderately raised prolactin, and hypothalamic amenorrhea with no clear functional cause, such as disturbed dietary habits, excessive exercise, or stress.
Keywords: Adolescents; Amenorrhea; Brain tumor; Craniopharyngioma; Female; Glioma; Gynecology; Pediatric and adolescent gynecology; prolactin